Multicolor multiphoton microscopy based on a nanosecond supercontinuum laser source. Issue 7 (12th February 2016) - Lefort, Claire; O'Connor, Rodney P.; Blanquet, Véronique; Magnol, Laetitia; Kano, Hideaki; Tombelaine, Vincent; Lévêque, Philippe; Couderc, Vincent; Leproux, Philippe
Abstract : Multicolor multiphoton microscopy is experimentally demonstrated for the first time on a spectral bandwidth of excitation of 300 nm (full width half maximum) thanks to the implementation a nanosecond supercontinuum (SC) source compact and simple with a low repetition rate. The interest of such a wide spectral bandwidth, never demonstrated until now, is highlighted in vivo : images of glioma tumor cells stably expressing eGFP grafted on the brain of a mouse and its blood vessels network labelled with Texas Red ® are obtained. These two fluorophores have a spectral bandwidth covering the whole 300 nm available. In parallel, a similar image quality is obtained on a sample of mouse muscle in vitro when excited with this nanosecond SC source or with a classical high rate, femtosecond and quasi monochromatic laser. This opens the way for (i) a simple and very complete biological characterization never performed to date with multiphoton processes, (ii) multiple means of contrast in nonlinear imaging allowed by the use of numerous fluorophores and (iii) other multiphoton processes like three‐photon ones. Abstract : Multiphoton imaging is usually performed with femtosecond Titanium Sapphire lasers (high repetition rate, small spectral bandwidth). Here we accomplished multiphoton imaging with a low‐rate nanosecond ultrabroadband source. Images are obtained with classical and supercontinuum sources for comparison. The interest of this last source, beyond its simplicity, robustness and low cost, stays in its spectral bandwidth between 600 and 2400 nm that opens new vistas for multiphoton imaging.